The relationship between educational and scientific regulatory interventions and socio-economic development in military conflict-affected countries: A Sustainable Development Goals perspective - Dariusz Krawczyk; Nadiia Artyukhova; Dmytro Svynarenko; Anna Vorontsova; Artem Artyukhov; Robert Rehak; Tetiana Vasylieva (Problems and Perspectives in Management)
Type of the article: Research Article AbstractThis study investigates the structural relationships between educational and scientific regulatory interventions and socio-economic development in countries affected by armed conflict and political instability, using the framework of Sustainable Development Goals (SDGs), specifically SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation and Infrastructure). Rather than focusing on regulatory interventions in a narrow administrative sense, SDG 4 is conceptualized as a reflection of national efforts to improve access to and quality of education, including institutional reforms, policy initiatives, and capacity-building measures in post-conflict settings. The analysis covers 16 countries affected by conflict and instability across Eastern Europe, including Ukraine; the Balkans (Albania, Bosnia and Herzegovina, Croatia, Montenegro, North Macedonia, Serbia, Slovenia); the Middle East (Israel, Jordan, Lebanon, Syrian Arab Republic, Turkey); and the South Caucasus (Armenia, Azerbaijan, Georgia), using data from 2011 to 2020. Employing multivariate confirmatory factor analysis (CFA), the study reveals statistically significant and conceptually meaningful covariances between the selected SDGs. The strongest relationship is observed between SDG 8 and SDG 9, underscoring the interdependence of economic growth, industrial development, and innovation. Moderate but significant correlations between SDG 4 and both SDG 8 and SDG 9 highlight the foundational role of education in enabling socio-economic recovery and technological advancement. Key indicators such as primary school completion, secondary and tertiary enrollment, employment in industry and services, and high-tech value-added production serve as measurable proxies for these dynamics. The findings emphasize the importance of aligning education policy with broader development strategies to support resilience and sustainable growth in fragile contexts. Acknowledgments and research fundingThis research was funded by the European Union grants “NextGenerationEU through the Recovery and Resilience Plan for Slovakia” (No. 09I03-03-V01-00130) and “Immersive Marketing in Education: Model Testing and Consumers’ Behavior” (No. 09I03-03-V04-00522/2024/VA). This research was also prepared as part of project 0124U000545.